2008
DOI: 10.4028/www.scientific.net/kem.373-374.670
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Nano-Copper and its Dispersive Behavior in Water

Abstract: In this paper, by measurement of zeta potential and particle size the surface modification of Cu nanoparticles in water was investigated at different pH values and different concentration of sodium dodecylbenzenesulfonate (SDBS) dispersant. The results show that the absolute value of zeta potential has very corresponding relation with particle size, and that the higher the absolute value of zeta potential and the smaller of the particle size are, the better dispersion and stability of copper nano-suspensions s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…When time variation is from 12 hours to 72 hours, the settlement volume changes little. All of these suggested that wettability and dispersion of modified nano-CaCO 3 in liquid paraffin have been stable and improving [7,8].…”
Section: Advanced Materials Research Vols 347-353mentioning
confidence: 99%
“…When time variation is from 12 hours to 72 hours, the settlement volume changes little. All of these suggested that wettability and dispersion of modified nano-CaCO 3 in liquid paraffin have been stable and improving [7,8].…”
Section: Advanced Materials Research Vols 347-353mentioning
confidence: 99%